Aleitamento materno em tempos de COVID-19: uma revisão de literatura (Revista Brasileira Multidisciplinar, 2024)
The COVID-19 pandemic damaged the global public health, including the practice of breastfeeding. In this context, the goal of this work is to review the literature in order to provide relevant information to guide the practice of multidisciplinary teams. To this end, a bibliographic survey was carried out in the databases PubMed, CAPES Periodical Portal, Cochrane, Virtual Health Library and SciELO, using the descriptors “Breastfeeding”, “Health Education” and “COVID-19” combined together. In total, 30 articles were selected, which were published in the last 4 years. It is noted that there are promises of viral transmissibility during breastfeeding, based on positive results in the detection of viral RNA in milk samples from sick mothers, but this contamination rate is low, even more so when health protocols are adopted to exclude external factors. As it is a recent condition, the social impacts of the disease and the immunizing benefits related to breast milk are still being predicted, especially after the implementation of vaccination schedules. On the one hand, there are already strong intentions that the health, especially the mental health, of the mother-baby dyad was harmed by the difficulty in contacting health services, but from another perspective the pandemic has become an opportunity to defend education as a public policy given the known protective benefits and evidence of passive immunization of newborns against the coronavirus. It is concluded that the benefits of breastfeeding are broad in the short and long term, and should be a practice defended by the entire multidisciplinary health team.Keywords: Breastfeeding; COVID-19; Health education.